1983
DOI: 10.1177/009164718301100305
|View full text |Cite
|
Sign up to set email alerts
|

Pretraining Variables in the Prediction of Missionary Success Overseas

Abstract: A set of twelve variables was obtained statistically in order to predict missionary success from a combination of pretraining data which included elements of personality, interpersonal skill, attitudes, and bio-graphical information. This data was gathered from structured interviews, open-ended references, and psychological tests available from each subject's application file. A screening sample of 111 vocational missionaries who had served overseas a minimum of one year was used to derive the predictors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Wickstrom (1978) demonstrated that boarding or nonboarding did not negatively affect a missionary kid's (MK's) self-esteem, but it was significantly affected by relationships with his or her parents. One aspect of Britt's (1983) research correlated the success of a group of missionaries working in Europe and their relationships with their fathers in early life. MK Consultation and Research Team/Committee on Research and Endowment (CART/CORE) identified warmth and closeness to one's father as positively correlated with an MK's return to overseas service as a vocational missionary (Andrews, 1995).…”
Section: Family Lifementioning
confidence: 99%
“…Wickstrom (1978) demonstrated that boarding or nonboarding did not negatively affect a missionary kid's (MK's) self-esteem, but it was significantly affected by relationships with his or her parents. One aspect of Britt's (1983) research correlated the success of a group of missionaries working in Europe and their relationships with their fathers in early life. MK Consultation and Research Team/Committee on Research and Endowment (CART/CORE) identified warmth and closeness to one's father as positively correlated with an MK's return to overseas service as a vocational missionary (Andrews, 1995).…”
Section: Family Lifementioning
confidence: 99%
“…32 Research on missionary performance has shown anxiety and moodiness as key indicators of performance. [33][34][35][36] More research is needed in the area of mental health of missionaries.…”
Section: Mental Healthmentioning
confidence: 99%
“…Humberto de Espinola (1985) found integrated thought processes to be important in cultural adjustment in a group of immigrants to Argentina. Britt (1983) found father absence before age 15 to be negatively related to psychological adjustment in a sample of missionaries. Both poor maternal care and father absence theoretically contribute to difficulties in object relations development.…”
mentioning
confidence: 91%
“…Finally, stress tolerance, flexibility, and a low need for control are conceptually related to the level of defense mechanisms used by an individual, and stress tolerance also implies good physical immunity, which has likewise been found to relate to object relations development (Cramer, Ford, & Blatt, 1988;Horner, 1991;McKay, 1991). Other studies (Britt 1983;Hammer, 1992;Redmond & Bunyi, 1993) have addressed the importance of interpersonal skills of various kinds. Object relations development is directly linked to the quality of relationships that a person can have (Fairbairn, 1952(Fairbairn, , 1954Mahler, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation